The Limits of Political Subjectivity: Hatice Sabiha Görkey and Women’s Representation in Early Republican Turkey - Çevik, Abidin (Fırat University, 2026)
This study focuses on the life and political activities of Sabiha Görkey, one of the first female members of parliament in the history of the Turkish Republic. The article explores how women's rights evolved and how their political representation changed during the transition from the Ottoman Empire to the Republic. It highlights how the political rights given to women during Atatürk’s era played a key role in transforming society.The right of women to participate in elections in the 1930s, and the election of the first female deputies to the Parliament in 1935, are analyzed within the framework of the Republic’s principles of modernization and equality. Görkey’s active involvement in parliamentary work, her roles in committees, and participation in various votes demonstrate that she stood out among the female politicians of the time. Although she did not deliver speeches from the rostrum, it is evident that she carried out her political duties with seriousness. Through Görkey’s individual biography, the study aims to analyze broader trends in women's political representation during the early Republican period. It also explores the reflections of women’s political participation in the contemporary press, and supports the findings with parliamentary records concerning Görkey’s contributions to legislative work. In addition to the existing literature on the period in question, newspapers have been used as primary sources to track developments in women’s rights and their portrayal in the media. The Official Gazette of the Grand National Assembly of Turkey (TBMMZC) has also served as one of the primary sources for tracking political developments. The research findings indicate that the 1935 election results—when women exercised their right to be elected for the first time—were closely monitored and reported by the press.

Bu çalışma, Cumhuriyet tarihinin ilk kadın milletvekillerinden Sabiha Görkey’in hayatı ve siyasi faaliyetlerini konu edinmektedir. Makalede, İmparatorluk’tan Cumhuriyet'e geçiş sürecinde kadın haklarının gelişimi ve kadınların siyasal alandaki temsiline dair yaşanan kırılmalar tarihsel bir perspektifle ele alınmış, özellikle Atatürk döneminde kadınlara tanınan siyasal hakların toplumsal dönüşüm açısından önemi vurgulanmıştır. 1930’lu yıllarda kadınların seçimlere katılım hakkı kazanması ve 1935 seçimleriyle birlikte Meclis’e ilk kez kadın milletvekillerinin girmesi, Cumhuriyet’in modernleşme ve eşitlik ilkeleri bağlamında değerlendirilmiştir. Görkey’in milletvekilliği süresince Meclis çalışmalarına aktif katılımı, komisyon görevleri ve çeşitli oylamalarda yer alması, dönemin kadın siyasetçileri arasında dikkat çeken bir duruş sergilediğini göstermektedir. Her ne kadar kürsü konuşmaları yapmamış olsa da siyasi faaliyetlerini ciddiyetle yürüttüğü anlaşılmaktadır. Çalışma, Görkey’in bireysel biyografisi üzerinden erken Cumhuriyet döneminde kadınların siyasal temsiline ilişkin genel eğilimleri analiz etmeyi, kadınların siyasal sürece katılımının dönem basınına yansımaları ve meclise giren ilk kadın milletvekillerinden Sabiha Görkey’in meclis çalışmalarına katılımı ve katkısı meclis zabıtlarıyla desteklemektedir. Çalışmaya konu olan döneme yönelik mevcut literatürün yanı sıra, kadın haklarıyla ilgili gelişmelerin dönem basınına yansımaları bağlamında gazeteler ana kaynak olarak kullanılmıştır. Yine siyasi gelişmelerin takibi için TBMMZC’si temel kaynaklardan bir diğeri olmuştur. Araştırma sonucunda kadınların ilk kez seçilme hakkını kullandığı 1935 seçim sonuçlarının özellikle basın tarafından yakından tespit edildiğini göstermiştir.
Siyasal Özneleşmenin Sınırları: Hatice Sabiha Görkey ve Erken Cumhuriyet Dönemi Kadın Temsiliyeti
Keywords: Women's Studies; Kadın Araştırmaları